Analysis of Sunflower phenology Helianthus annuus L. dwarf variety / Análise da fenologia do Girassol Helianthus annuus L. variedade anão - Alverlan da Silva Araújo; Diego Jorge da Silva; Adriely Vital de Souza Silva; Isabelle Cristina Santos Magalhães; Rubens Pessoa de Barros (Universidade Estadual de Alagoas, 2018)
Originally from North America, the sunflower, Helianthus annus L., is an annual dicotyledon, adapted to the most diverse edaphoclimatic conditions, cultivated in all the continents. In the Northeast of Brazil, it has been tried to establish practices of sunflower cultivation that allow its exploitation under rational and economic techniques, mainly because it is a plant of great nutritional requirement. The objective of this work was to know the phenological development of the sunflower Helianthus annuus L. in different types of animal manure treatments. The experiment was carried out in a greenhouse located at the State University of Alagoas- UNEAL Campus I from October 2016 to January 2017, the experimental design was completely randomized with four treatments (soil with bovine manure, soil with goat manure, soil with manure and soil without manure) and five replicates. According to the results obtained it was verified that there was a good germination index of the seeds of sunflower - GI with 95%. The results showed that there was no significant difference in the phenological development of sunflower plants grown in the different types of organic manure rich in animal manure, considering the comparison with sunflowers grown in soil without manure. The sunflower had a good development with the natural fertilizers, and the substrates used allowed to observe that this development was the result of material rich in organic matter and nutrients necessary to the plant.